THE APPLICATION OF CONSTRAINT PROPAGATION TECHNIQUE FOR CONCEPTUAL AIRCRAFT DESIGN - R Zain; C Bil (Mesin, 2009)
In conceptual aircraft design phase, the aircraft configuration and several design variables are frequently changed and starting points are depended on any most probable design conditions. Therefore, it is required a design tool having flexibility to response to different starting points. The implementation of the constraint propagation supported by an object-oriented programming could result in a computer application that considerably accommodates the need of flexibilities. Moreover, the implementation of some graphical user-interfaces and filter are not only to make it become user-friendly but also it may perform good filters to validate all inputs from the user. Use case diagram and class diagram are utilized as tools for designing the computer application using Microsoft Visual C++ 6. For a case study, some relations of basic aircraft geometry are implemented by selecting the six constraints and fourteen design variables. The result of this work shows that the application of constraint propagation is right and proper to handle any frequent changes during the conceptual design phase.